Intervista a Danilo Prosperi, curatore di Polo Museale dell’Abruzzo 3D Project. I Capolavori dell’arte abruzzese in 3D e Virtual Tour dei principali Musei dell’Abruzzo. - Archeomatica, Redazione (Archeomatica, 2018)
The project, born from an idea of the Polo Museale dell'Abruzzo, in the person of the Director Dott.ssa Lucia Arbace, under the supervision of the RUP of the Project, Dr. Giulia Tortoriello, entrusted to ARCHIMETRIA Group, a team of professionals who work in the field of 3D documentation and technological innovation applied to cultural heritage, led by Arch. Danilo Prosperi, founder and CTO of the study, was born in July 2017 and ended in March 2018. The aim of the project is to enhance and disseminate on a global scale the knowledge of the major Abruzzo museums and the extraordinary masterpieces of art and archeology exhibited in it, through the use of 3D technologies (scans and digital 3D reproductions in HD, Virtual Immersive and interactive HD tours, use of 3D viewers for virtual reality, 3D printing, etc.) and through the publication of contents in all areas of the official website of the Abruzzo Museum Complex, SketchFab and Google Maps and Street View.